Spatio-Temporal Pattern Analysis of Forest Fire in Malang based on Remote Sensing using K-Means Clustering - Kirana, Annisa Puspa; Astiningrum, Mungki; Vista, Candra Bella; Bhawiyuga, Adhitya; Amrozi, Aris Nur (Future Science / FSH-PH Publications, 2023)
Forest and land fire significantly impact the balance of the environment, such as haze pollution, destruction of ecosystems, the high release of carbon in the air, deterioration of health, and losses in various other fields. Based on these factors, developing an early warning system is essential to prevent forest fires, especially in forest and land areas. One of the data that can be used to monitor areas where there are frequent fires is hotspot data taken from the NASA MODIS Fire satellite. Data mining techniques are carried out to process the hotspot data so that the distribution of hotspot swarms is obtained. The data on the distribution of the clustering of hotspots are used to detect areas that are prone to fire from year to year. This study used the K-Means clustering algorithm. The data used in this study is hotspot data from Malang District, Indonesia. The range of hotspot data from January 2018 to June 2022. We use Silhouette coefficient testing to get the best number of classes in the cluster—this study's most recent application of the K-means clustering method to analyze hotspot distribution in a spatial-temporally. We use hotspot data in Malang's forest and land area using hotspot confidence levels >80%.